2023
DOI: 10.1101/2022.12.29.22284005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-Coronary Artery Bypass Graft Complications; Potential Causes and Risk Factors

Abstract: Background: Cardiovascular disease (CVD) remains the leading cause of death worldwide despite the coexistence of the current COVID-19 pandemic. Current emergency management involves revascularization of the coronary arteries. Aims: Retrospectively evaluating the association between the used number of shunts and postoperative complications. And to evaluate the potential pre/postoperative risk factors for complications development. Objectives: Several complications are reported after coronary artery bypass graft… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Post-MI changes include early and late pathophysiological changes, early post-MI complications include ventricular rupture, aneurism, arrythmia, sudden cardiac arrest and death [11][12][13] . However, the late changes include pericarditis, pneumonitis, pleuritis, and post infarction cardiosclerosis and dyskinesia [14,15] . Such manifestations are associated with some laboratory and instrumental changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-MI changes include early and late pathophysiological changes, early post-MI complications include ventricular rupture, aneurism, arrythmia, sudden cardiac arrest and death [11][12][13] . However, the late changes include pericarditis, pneumonitis, pleuritis, and post infarction cardiosclerosis and dyskinesia [14,15] . Such manifestations are associated with some laboratory and instrumental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle changes have a huge impact on the overall health of the cardiovascular system [3,4]. Unfortunately, sedentary lifestyle is seen in majority of myocardial infarction, which is associated with development of several predisposition factors for cardiovascular events such as dyslipidaemia, insulin resistance, and central obesity or visceral obesity [5][6][7][8][9]. Collectively, these early signs of disturbance of cardiovascular homeostasis are ignored to provoke the progression of dyslipidaemia and insulin resistance to reach enough levels to induce the emergence of cardiovascular events such as MI [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential pathophysiological pathway is multifactorial and involves autophagy dysfunction, upregulated sympathetic tone, mitochondrial dysfunction, inflammation, abnormal atrial conduction, and systemic inflammatory response indicated by elevated C-reactive protein and leukocytes [2231]. Some studies showed that on-pump CABG surgery has higher risk of atrial fibrillation than off-pump [3237].…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of post-myocardial infarction (MI) changes remain unclear and require further investigation. Consequently, determining the precise life expectancy of MI patients remains challenging [6][7][8]. MI involves necrosis of myocardiocytes and disruption of the heart tissue's essential functions, including automaticity, conduction, and contractility.…”
Section: Introductionmentioning
confidence: 99%